Język muzyki jako ważny element świętowania liturgicznego (zarys problemu) - Celary, Ireneusz (Studia Pastoralne, 2026)
The paper presents the issue of the language of music which is a very important element of liturgical celebration. First section of the article is focused on music as one of the most important components of culture and a subtle way of communication. Music has been present in human life from the beginning, during work, play and free time. Surly it was combined from the beginning with dance and words. Originally it served for practical purposes – it helped with group work as a form of communication. Later it became also element of common identity, and with time it was part of the arts. Next part of the article is concentrated on the role of music in liturgy of the Church. Since the Apostolic Age it has been treated as a gift of the Holy Spirit, like preaching kerygma. Religious music is an art which takes its inspiration from God’s subject, His revelation in the world or different forms of religious life of the community of faith. Today, according to the teachings of II Vatican Council, the liturgy not only should be open for music from its nature, but it should demand it. Liturgical music is not only an ornament of the celebration, but it should be integrated with holy rites. In the final part of the article, some pastoral proposition are presented which should contribute to rising up of the purpose of liturgical music: God’s glory, sanctifying of faithful and building of the community of the Church.